Change in Acetabular Cup Orientation From Supine to Standing Position and Its Effect on Wear of Highly Crosslinked Polyethylene - Teeter, Matthew G.; Goyal, Prateek; Yuan, Xunhua; Howard, James L.; Lanting, Brent A. (The Journal of arthroplasty, 2018)
The purpose of this study is to measure acetabular cup position and wear of the highly crosslinked polyethylene liner in the supine and standing position for patients at a minimum of 10 years after the operation. A total of 38 patients were recruited at a mean of 12.5 years after the operation. All patients received a single acetabular cup design with a highly crosslinked liner and a 28-mm cobalt-chromium femoral head. Patients underwent supine and standing radiostereometric examinations in which the X-ray sources and detectors were positioned to obtain an anterior-posterior and cross-table lateral radiograph. Acetabular cup position and the three-dimensional wear rate were measured from the radiographs, and outcome scores were recorded for each patient. Anteversion significantly increased (P < .0001) a mean of 12° from supine (15.1° ± 10.4°) to standing (27.2° ± 10.5°) position. Inclination also significantly increased (P = .001) a mean of 2° from supine (44.4° ± 6.8°) to standing (46.3° ± 7.7°) position. There was no difference (P = .093) in wear rate between supine (0.067 ± 0.070 mm/y) and standing (0.073 ± 0.074 mm/y) positions. There were no correlations between cup orientation and wear rate in either position. Highly crosslinked polyethylene is a forgiving bearing material. Although adherence to the traditional acetabular position target zone is recommended, ensuring hip stability and consideration of the patient's functional position are also important objectives to consider for the acetabular position.